Intervención optométrica en paciente masculino de 10 años de edad con visión borrosa asociada a la endoforia. - Mera Robelli, Ramon Orlando (2024)
The behavior of a patient with ocular endophoria is very complex, this is a functional disorder in which the patient is not able to maintain the coordination of the two eyes in near vision or in distance vision due to a high ocular deviation. There is a tendency to turn one eye inward (endophoria) intermittently both when looking at distance and up close. The etiology of this ocular condition may be purely due to a binocular alteration or decompensation of the patient. This causes the patient to have farsightedness, due to visualization as a consequence of prolonged work on a computer. These patients who suffer from it tend to strain their eye muscles a lot to keep them parallel and be able to see correctly. The main objective of this investigative work is to assess the patient's behavior regarding her low vision associated with endophoria. Within the patient's clinical data, he refers to constant headache, severe pain in his right eye when making visual effort and abnormal intolerance to light which does not allow him to carry out his activities normally, he manifests headache. At the time of performing his corresponding examinations, we realized through the cover test that the patient had an epiphora in the eyeball due to discomfort in natural light. Also, through this cover test we were able to confirm the presence of a deviation of the right eye towards the nasal part. We reached an important conclusion through this optometric clinical case, the headache is a product of the presence of ocular phorias, in this case the endophoria of the right. eye, the optometric assessment through a refraction allowed the correction of the visual state by making lenses protection against light.